Posterior circulation stroke following mild head injury - Datta, SGS (Indian Journal of Neurotrauma, 2008)
A young soldier sustained clinically mild head injury. He developed complication 24 hrs after head injury in the form of left cerebellar infarct with acute hydrocephalus. In spite of best efforts to resuscitate the patient and to relieve the raised intra cranial pressure, he succumbed to his complications. The case report highlights posterior circulation stroke as a rare complication of mild head injury.
Keywords: mild head injury; posterior circulation stroke